Transforming Insights into Action: The Influence of Business Analytics on Corporate Strategy Development - Begum, Nazma; Karim, Sheikh Rezaul; Ali, Md. Mokshud (International Journal of Business and Economics, 2024)
The revolutionary impact of business analytics on corporate strategy in modern firms is investigated in this research paper. Integrating analytics into strategic planning has become essential for gaining a competitive edge in a time of rapid technological innovation and data abundance. The significance of this study is in its capacity to clarify how data-driven decision-making can improve organizational performance and flexibility in a changing marketplace. The main goal of this study is to investigate the effects of employing business analytics in the development of corporate strategies, with a particular emphasis on how these processes affect decision-making and the overall efficacy of strategic initiatives. By analyzing these dynamics, the study hopes to offer firms looking to use analytics for strategic success practical insights. The scope of the study includes a thorough investigation of how business analytics impacts many aspects of corporate strategy, such as risk management, customer relationship management, and operational efficiency. The main issue discussed is the discrepancy between conventional strategic planning techniques and the requirement for a more data-centric strategy that can adapt to changing market conditions. The idea that better strategic results can result from the efficient application of business analytics forms the basis of the theoretical framework that directs this study. Using secondary data sources including case studies, industry reports, and scholarly literature, a qualitative research methodology is used to accomplish these goals. This methodology makes it easier to conduct a comprehensive analysis of current business analytics methods and knowledge in strategic situations. Organizations that successfully incorporate analytics into their strategic planning procedures report better performance metrics and increased decision-making capabilities, according to the main findings of the analysis. Potential biases in secondary data and the difficulty of extrapolating results across several businesses are drawbacks, though. In terms of theory and practice, this study has consequences. Theorists can better grasp how business analytics may transform strategic frameworks, and practitioners can learn about the most effective ways to put data-driven plans into reality. The findings of this study ultimately highlight how important it is for businesses to develop a strong data culture that values analytics as a fundamental part of their strategic decision-making procedures.